(untitled) (JURNAL ADMINISTRASI PUBLIK, 2023)
This study aims to examine the effect of mutations on employee performance at the Regional Secretariat of South Bolaang Mongondow Regency. The survey method is used to take samples from the population and collect data quantitatively. The data was processed from the results of distributing questionnaires to employees of the Regional Secretariat of South Bolaang Mongondow Regency with a total population of 94 people and a sample of 48 respondents. The basic linear regression analysis approach was applied in this study. The results showed that there was a positive influence between mutations and employee performance, so that the better the mutation implementation, the better the employee performance.